(untitled) (Annals of Bangladesh Agriculture, 2025)
Holy Basil (Ocimum sanctum L.) is a valuable herb due to its medicinal, ornamental and culinary applications. The conventional propagation methods are unsuitable due to seed dormancy and slow growth. This study aimed to establish an optimized in vitro regeneration method using nodal segments obtained directly from mature plant to achieve rapid propagation of O. sanctum. The sterilized explants were placed on the Murashige and Skoog (MS) medium containing various concentrations of 6-Benzylaminopurine (BAP) and Kinetin (KIN) (0.5, 1.0, 1.5 and 2.0 mg/L) to promote shoot proliferation. Subsequently, indole butyric acid (IBA) and indole acetic acid (IAA) (0.5, 1.0, and 1.5 mg/L) were used on MS medium for the induction of roots. The results showed that the highest percentage of shoot response (92.7%), shoots per explant (6.5) and length of shoots (5.63cm) were observed with a concentration of 1.5 mg/L BAP, highlighting the efficiency of the in vitro culture method. The highest root induction (90.0%) and roots per explant (5) were achieved using 1.0 mg/L IBA. Hardening media were prepared using various combinations of garden soil, sand, and farmyard manure (FYM). The highest survival rate (90%) was observed in a combination of garden soil and sand in a 1:1 ratio. However, the in vitro culture method, as demonstrated in this study, is a highly efficient approach for the rapid propagation of O. sanctum. Ann. Bangladesh Agric. 28(2): 57-69